Association of Peripheral Plasma Neurotransmitters with Cognitive Performance in Chronic High-altitude Exposure. (21st May 2021) - Zhong, Zhifeng; Zhou, Simin; Xiang, Bin; Wu, Yu; Xie, Jiaxin; Li, Peng
Graphical abstract: Highlights: Participants' peripheral plasma neurotransmitters were altered at high altitude. The neurotransmitters were associated with cognitive impairment at high altitude. Central and peripheral neurotransmitters mediate hypobaric hypoxia exposure in rats. Neurotransmitters of peripheral were related to central in hypobaric hypoxia in rats. Abstract: Long-term living at high altitude causes significant impairment of cognitive function. Central neurotransmitters are potential mediators of cognitive performance. We aimed to determine whether there were significant associations between select peripheral plasma neurotransmitters and cognitive performance in humans with chronic high-altitude (HA) exposure and to determine the association between peripheral plasma neurotransmitters and brain neurotransmitters in rats after chronic hypobaric hypoxia (HH) exposure. We demonstrated that 3, 4-dihydroxy-L-phenylalanine (DOPA), dopamine, serotonin, 5-hydroxyindole-3-acetic acid (5-HIAA) and GABA in the peripheral plasma were associated with cognitive performance in humans with HA exposure. Consistent with this result, peripheral plasma DOPA, dopamine, serotonin, 5-HIAA and glutamate were associated with brain neurotransmitter levels after chronic HH exposure in rats. These results provide experimental data indicating that neurotransmitter levels and cognitive performance are modified in chronic high-altitude exposure, with a possible causal effect.